The Concept of Assessment as Learning: Educator Perspectives From a Phenomenological Lens - Rastegar, Babak; Salavati Nooshabadi , Mitra (Assessment and Practice in Educational Sciences, 2024)
This study aimed to explore educators’ perspectives on the concept of assessment as learning through a phenomenological lens to understand how it is conceptualized, enacted, and experienced within classroom contexts. A qualitative phenomenological research design was employed. Data were collected through semi-structured interviews with 27 educators from various schools in Tehran. Participants were purposefully selected to ensure diverse teaching backgrounds. Interviews were audio-recorded, transcribed verbatim, and analyzed thematically using NVivo software. Data collection and analysis continued until theoretical saturation was reached. Three main themes emerged from the analysis: (1) Pedagogical foundations of assessment as learning, including emphasis on self-regulation, formative feedback, learner autonomy, integrated assessment, shifts in educator roles, and purposeful assessment design; (2) Challenges and constraints such as institutional barriers, professional development needs, student readiness, resource limitations, assessment culture, and equity concerns; and (3) Perceived outcomes and impacts including deepened learning, increased student engagement, enhanced motivation, improved metacognition, and strengthened classroom relationships. Educators recognized the potential of assessment as learning to foster learner agency and deeper engagement but identified significant systemic and cultural obstacles that limit its full implementation. The study highlights educators’ sophisticated understanding of assessment as learning and its benefits for student autonomy and metacognitive development. However, institutional, cultural, and resource-related constraints pose challenges that require systemic support. Professional development, collaborative communities, and aligned policies are critical to enable meaningful adoption of assessment as learning. These findings provide valuable insights for educational stakeholders aiming to promote learner-centered assessment practices.